(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to helminths of poultry. This article provides an in-depth analysis of the scientific literature on helminths in poultry. Methods for studying helminths are described in detail. It is proposed to implement a number of preventive measures in order to prevent infection of poultry with helminthic diseases and reduce the impact on food safety. In particular, to minimize the damage caused by helminths to poultry, regular monitoring, early detection and appropriate treatment or preventive measures are desirable.